Social Community in the Quran (A Study of Muhammad Abduh's Interpretation in Tafsir Al-Manar) - Muhammad Zubir (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study offers Muhammad Abduh's ideas about awakening and advancing the backwardness of Islamic social communities which, left behind from western civilization from the perspective of the Koran. Abduh is a contemporary commentator and also a reformer of Islamic thought in the 19th century AD. This research is a library research using the maudhu'i interpretation research model. Based on Muhammad Abduh's interpretation of the verses of social community, it was found: 1). The concept of ummatan wasathan (middle society) is the best profile of society that should be applied by Muslims; 2). Ummah wahidah is an affirmation that humans are social creatures to live together and need each other; 3). Khairu ummah, is a guide to become the best and superior society by doing: al-amru bi al-ma''ruf, al-nahi 'an al-munkar, believing in Allah SWT and sticking to Islamic law; 4). The progress and decline of the Islamic community are greatly influenced by the efforts and awareness of the Islamic community to rise up and change their own destiny; and 5). Islam is present as the religion of rahmatan lil'alamin shalihun li kulli era wa al-makan. Several factors cause the backwardness and decline of the Islamic social community in various fields of life from other communities: 1). Abandoning the teachings of the Qur'an and Sunnah; 2). There is no unity and integrity of the people; and 3). Widespread understanding of jumud and taklid in religious matters. Penelitian ini menawarkan ide pemikiran Muhammad Abduh dalam membangkitkan dan memajukan keterbelakangan komunitas sosial masyarakat Islam yang jauh tertinggal dari peradaban Barat perspektif al-Quran. Abduh adalah seorang mufassir kontemporer dan juga seorang tokoh pembaharu kebangkitan pemikiran dalam Islam abad ke 19 M. Penelitian ini merupakan penelitian library research dengan menggunakan model penelitian tafsir maudhui. Berdasarkan penafsiran Muhammad Abduh tentang ayat-ayat komunitas sosial, ditemukan: 1). Konsep ummatan wasathan (masyarakat pertengahan) merupakan profil masyarakat terbaik yang seharusnya diterapkan oleh umat Islam; 2). Ummah wahidah merupakan penegasan bahwa manusia adalah makhluk sosial untuk hidup bersama dan saling membutuhkan; 3). Khairu ummah, merupakan tuntunan untuk menjadi masyarakat terbaik dan unggul dengan melakukan: al-amru bi al-maruf, al-nahi ‘an al-munkar, beriman kepada Allah SWT dan berpegang teguh dengan syariat Islam; 4). Kemajuan dan kemunduran masyarakat Islam sangat dipengaruhi oleh usaha dan kesadaran masyarakat Islam untuk bangkit dan merubah nasib sendiri; dan 5). Islam hadir sebagai agama rahmatan lilalamin shalihun li kulli zaman wa al-makan. Beberapa faktor penyebab keterbelakangan dan kemunduran komunitas sosial Islam dalam berbagai bidang kehidupan dari komunitas lain: 1). Meninggalkan ajaran al-Quran dan Sunnah; 2). Tidak terjalinnya persatuan dan kesatuan umat; dan 3). Menyebarluasnya paham jumud dan taklid dalam persoalan agama.